1992
DOI: 10.1097/00000658-199205000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Juxtarenal Aortic Occlusion

Abstract: The authors' experience with 113 aortic occlusions in 103 patients during a 26-year period (1965 to 1991) is reviewed. The authors found three distinct patterns of presentation: group I (n = 26) presented with acute aortic occlusion, group II (n = 66) presented with chronic aortic occlusion, and group III (n = 21) presented with complete occlusion of an aortic graft. Perioperative mortality rates were 31%, 9%, and 4.7% for each respective group and achieved statistical significance when comparing group I with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…All of our patients had CAIO secondary to atherosclerotic aortoiliac occlusive disease, but other causes of CAIO such as embolism, dissection and aortitis have also been described. 1,15,16 We did not see any cases of SRO, but Tapper et al 9 have described an interesting series of 66 patients with CAIO, in which 10 patients (15%) had SRO, with a mortality rate of 9%.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…All of our patients had CAIO secondary to atherosclerotic aortoiliac occlusive disease, but other causes of CAIO such as embolism, dissection and aortitis have also been described. 1,15,16 We did not see any cases of SRO, but Tapper et al 9 have described an interesting series of 66 patients with CAIO, in which 10 patients (15%) had SRO, with a mortality rate of 9%.…”
Section: Discussionmentioning
confidence: 75%
“…1,8,9 Currently, a diagnosis of CAIO is still an absolute indication for surgical treatment in patients with aortoiliac occlusive disease, because the endovascular technique still suffers from limitations that impede adequate treatment of these patients, although there are already some recent studies that have reported promising results. 11,12 On the other hand, as endovascular techniques are being more and more widely adopted for treatment of patients with aortoiliac occlusive disease, open surgery has come to be reserved for patients with more severe forms of occlusive disease, such as CAIO.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations